Analysis of sensory characteristics and bacterial community structure of low-temperature Daqu - ZHAO Heng, CAI Wenchao, YU Peirong, CHEN Wei, SHAN Chunhui, ZHANG Haibo, GUO Zhuang (Zhongguo niangzao)
In this study, the sensory characteristics and bacterial community structure of low-temperature Daqu from Liangshan region of Shandong province were determined using electronic nose and electronic tongue technology and MiSeq high-throughput sequencing technology, and the correlation was analyzed. Compared with the bacterial community of low-temperature Daqu in Xiangyang region, Bacillus strains were isolated and identified by pure cultivation and molecular biology techniques. The results showed that the volatile aroma components of Liangshan low-temperature Daqu mainly comprised sulfides, ethanol, and aldehydes/ketones, saltiness and umami tastes were prominent, while sourness and umami aftertastes were weak. The dominant bacterial genera were mainly Pediococcus (25.33%), Weissella (21.58%), and Companilactobacillus (5.27%). Pediococcus, Lactiplantibacillus, and Levilactobacillus showed a significant positive correlation with bitterness or bitter aftertaste (P<0.05). Compared to Xiangyang low-temperature Daqu, the bacterial community richness in Liangshan low-temperature Daqu was lower, with less Bacillus and more lactic acid bacteria, and the common bacterial groups included Bacillus, Kroppenstedtia, and some lactic acid bacteria. A total of 8 strains of Bacillus were isolated and identified from Liangshan low-temperature Daqu, including 3 strains of Bacillus licheniformis, 2 strains of Bacillus sonorensis, 2 strains of Bacillus paralicheniformis, and 1 strain of Bacillus haynesii.